RANCANG BANGUN SISTEM MONITORING DAN PROTEKSI PADA PEMBANGKIT LISTRIK TENAGA SURYA DAN BAYU BERBASIS INTERNET OF THINGS - Adi Fauzul (Jurnal Informatika dan Teknik Elektro Terapan, 2026)
Solar and Wind Power Plant (Hybrid) is one of the strategic solutions to support small-scale energy independence, especially in areas that require independent electricity supply. This study aims to design and implement a monitoring system based on PZEM-004T and PZEM-017 by integrating IoT technology effectively and efficiently and evaluating the performance of the developed monitoring and IoT system in terms of data accuracy, communication reliability, and cloud data for system operators at Warung Kopi Gus Kulon. The method used is direct observation in the field to monitor the actual condition of the Solar and Wind Power Plant system consisting of solar panels and DC generators. This study successfully designed and realized a monitoring system on the Solar and Wind Power Plant (PLTH) at Warung Kopi Gus Kulon by utilizing the PZEM-004T and PZEM-017 sensors. The test results show that the system is able to work stably and supports comprehensive monitoring of the PLTH condition.